Fueling fibrosis: BCAT1 links branched-chain amino acid metabolism to collagen production - Marco Ronfini; John W. Elrod (Journal of Clinical Investigation, 2026)
Fibrosis remains a major driver of organ dysfunction, yet the metabolic programs that sustain extracellular matrix production are incompletely understood. In this issue of the JCI , Takizawa and colleagues identified branched-chain amino acid transaminase 1 (BCAT1) as a crucial metabolic regulator of fibroblast activation and fibrosis in a model of cardiac fibrosis. Their observations were corroborated by analyses of datasets from patients with heart failure with preserved ejection fraction and metabolic dysfunction–associated steatohepatitis. They report that by coupling mechanical and TGF-β signaling to a proline biosynthesis and utilization program, BCAT1 enhanced collagen production in activated cardiac fibroblasts. These findings place branched-chain amino acid metabolism as a pivotal contributor to fibroblast activation and highlight BCAT1 as a promising therapeutic target for fibrotic disease.